Food Security Office Strategies for Addressing Stunting Issues in Medan City - Pardede, Piki Darma Kristian; Saraan, imanuddinMuhammad Imanuddin Kandias (Talenta Publisher, 2023)
Food availability is one of the important aspects in overcoming stunting. Food is a source of nutrition that can prevent stunting. Food diversity requires the development of a system that can guarantee the availability of food diversity. The purpose of this study was to describe the role of food availability in stunting prevention. The research method used is descriptive qualitative. The results show that efforts to strengthen food security by increasing the availability of diverse food requires collective awareness that places food as an important part of overcoming stunting. Increasing food production is a basic need by building a sustainable food system. Meanwhile, in increasing awareness of fostering a healthy culture, the intensity of education and socialization needs to be increased to encourage the importance of food for health development.